2012
DOI: 10.1080/1745039x.2012.740309
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of fibre sources and molecular weight distribution of fibre fractions in ileal digesta of growing pigs

Abstract: Seven post-valve T-caecum cannulated growing pigs were used in a change-over experiment with four diets and four 14-day periods to evaluate the total tract apparent digestibility (TTAD) and the ileal apparent digestibility (IAD) of diets with inclusion of chicory forage (CFO), sugar beet pulp (SBP), wheat bran (WB) and grass meal (GM), as well as the TTAD of the mentioned fibre sources. Moreover, this experiment evaluated the molecular weight distribution of soluble non-starch polysaccharide (NSP) fractions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…This suggests that the positive correlation observed between the proportion of propionic acid in ileal digesta and the intake of arabinose mainly can be explained by fermentation of arabinose originating from SBP. Ivarsson et al (2012b) observed differences in molecular weight distribution between pectins in diets CFO and SBP, and Ivarsson et al (2012c) showed that there are strong correlations between molecular weight distribution and the proportion propionic and acetic acid, which suggests that both the building blocks and the molecular weight distribution of pectin can explain the differences in SCFAs between the CFO and SBP. This indicates that the bacterial degradation of pectin is selective and dependent on the molecular weight.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This suggests that the positive correlation observed between the proportion of propionic acid in ileal digesta and the intake of arabinose mainly can be explained by fermentation of arabinose originating from SBP. Ivarsson et al (2012b) observed differences in molecular weight distribution between pectins in diets CFO and SBP, and Ivarsson et al (2012c) showed that there are strong correlations between molecular weight distribution and the proportion propionic and acetic acid, which suggests that both the building blocks and the molecular weight distribution of pectin can explain the differences in SCFAs between the CFO and SBP. This indicates that the bacterial degradation of pectin is selective and dependent on the molecular weight.…”
Section: Discussionmentioning
confidence: 93%
“…However, it should be noted that the ileal digestibility in general is higher for pectins than for arabinoxylans (Noblet and Le Goff, 2001). However, Ivarsson et al (2012b), reported a similar ileal digestibility of dietary fiber, NSP and xylose in the GM diet as the SBP and CFO diet. Consequently, a high amount of microbial digested NSP in the present study can be linked to diets GM, SBP and CFO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, dietary pectin has been shown to induce HSP expression in rat intestine (37). The pigs in the present study were fed chicory pectin (in a cereal-based diet), which can be partially utilized in the distal ileum of the pig, with digestibility values ranging from 10 to 40% (13,23). It may thus contribute to strong ileal HSP expression.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of NDF effect on ileal digestibility of isolated proteins such as casein and SPC has been previously reported (Ivarsson et al . ; Mariscal‐Landín et al . ).…”
Section: Discussionmentioning
confidence: 99%